Development and validation of a self-regulation scale within the German version of the Early Development Instrument - Sabine Georg; Bernd Genser; Joachim Fischer; Steffi Sachse; Freia De Bock (BMC, 2023)
Abstract Background Early childhood self-regulation (SR) is key for many health- and education-related outcomes across the life span. Kindergarten age is a crucial period for SR development, and within this developmental window, potential SR difficulties can still be compensated for (e.g., through interventions). However, efficient measurement of SR through brief, comprehensive, and easy-to-use instruments that identify SR difficulties are scarce. To address this need, we used items of an internationally applied kindergarten teacher questionnaire-the Early Development Instrument (EDI) - to develop and validate a specific SR measurement scale. Methods The psychometric evaluation and validation of the selected SR-items was performed in data collected with the German version of the EDI (GEDI), in two independent data sets - (a) the development dataset, with 191 children, and b) the validation dataset, with 184 children. Both included three- to six-year-old children and contained retest and interrater reliability data. First, three independent raters-based on theory-selected items eligible to form a SR scale from the two SR-relevant GEDI domains "social competence" and "emotional maturity". Second, exploratory and confirmatory factor analysis using structural equation modeling examined the item structure across both data sets. This resulted in a defined SR scale, of which internal consistency, test-retest and interrater reliability, cross-validation, and concurrent validity using correlation and descriptive agreements (Bland-Altman (BA) plots) with an existing validated SR-measuring instrument (the Kindergarten Behavioral Scales) were assessed. Results Confirmatory factor analysis across both data sets yielded the best fit indices with 13 of the GEDI 20 items initially deemed eligible for SR measurement, and a three-factor structure: a) behavioral response inhibition, b) cognitive inhibition, c) selective or focused attention (RMSEA: 0.019, CFI: 0.998). Psychometric evaluation of the resulting 13-item-GEDI-SR scale revealed good internal consistency (0.92), test-retest and interrater reliability (0.85 and 0.71, respectively), validity testing yielded stability across populations and good concurrent validity with the Kindergarten Behavioral Scales (Pearson correlation coefficient: mean 0.72, range 0.61 to 0.84). Conclusions The GEDI contains 13 items suitable to assess SR, either as part of regular EDI developmental monitoring or as a valid stand-alone scale. This short 13-item (G)EDI-SR scale may allow early detection of children with SR difficulties in the kindergarten setting in future and could be the basis for public health intervention planning. To attain this goal, future research should establish appropriate reference values using a representative standardization sample.